ANALISIS INOVASI ROTI 7 LAPIS (RESPONSE TIME 7 MENIT LAYANAN PEMADAMAN KEBAKARAN GRATIS) DI KOTA SURABAYA DALAM PERSPEKTIF NEW PUBLIC SERVICE - Fitriana, Aulia Regita Dewi (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The "Roti 7 Lapis" innovation by Surabaya Fire and Rescue Department (DPKP) aims to accelerate fire fighting response with a target time of 7 minutes, at no cost, to reduce material losses and casualties. The program not only focuses on efficiency, but also builds community involvement in fire prevention, in line with New Public Service (NPS) principles that emphasize inclusivity, equity, and collaboration. "Roti 7 Lapis" manages fire risk holistically through cross-sector collaboration and the latest technology. Its implementation is supported by strict regulations and a transparent reporting system that ensures accountability and service effectiveness. Development recommendations include increasing community participation, strengthening transparency, and further integrating technological innovations. In the context of growing urbanization, these measures aim to improve the sustainability and effectiveness of the program in maintaining the safety and well-being of Surabaya's citizens.